Persfektif Ruang Kalkulasi Dalam Implementasi Parkir Elektronik (E-Parking) di Jalan Braga Kota Bandung - Hilman Rahmatulloh; Sonny Yuliar (Jurnal Sosioteknologi, 2023)
The on-street parking retribution generates a significant income for Bandung City’s local revenue. At the implementation level, agents who directly relate to the public (street-level bureaucrats) produce behavior contrary to the policy’s objective. In developing this behavior, the agent performs calculations that, in the process, involve non-human materials. This study will show how agents calculate space when dealing with the dilemmas faced in the practice of the e-parking parking policy. This study uses a qualitative method with the theoretical framework of Actor-Network Theory (ANT) as an analytical tool to describe the role of actors from both human and non-human perspectives in the calculation space. From the perspective of the calculation space, several concerns can be explored and considered in the implementation of the e-parking policy. Not even at street-level bureaucrats, behaviors contrary to objectives also occur at the agent level. The recommendation policy can be improved by considering the heterogeneous associations between human and non-human actors and the calculations and translations that occur through these heterogeneous associations.